2020
DOI: 10.1038/s41598-020-78924-9
|View full text |Cite
|
Sign up to set email alerts
|

Cu-chitosan nano-net improves keeping quality of tomato by modulating physio-biochemical responses

Abstract: Minimizing the post-harvest losses in fruits and vegetables is one of the challenging tasks in agriculture. To address this issue, we report nano-net of Cu-chitosan nanoparticles (Cu-chitosan NPs) which has the ability to extend the shelf-life of stored tomato. The application of Cu-chitosan NPs (0.01–0.04%) significantly curtailed microbial decay (< 5 versus > 50% in control), physiological loss in weight (14.36 versus 28.13% in control), respiration rate (0.01173 versus 0.01879 g CO2 kg−1 h−1) and main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 37 publications
6
33
1
Order By: Relevance
“…Some recent studies reported that fruit coated with Cs were prevented from reducing in weight, water vapor transmission rate and O 2 /CO 2 by increasing surface and interface roughness and due to a smaller pore size, thus preventing the percentage of weight loss [41]. Menna et al [25] reported Cu-chitosan nano significantly prevented weight loss in tomato during 21 days storage, which is in accordance with our study. Furthermore, chitosan/nano-TiO 2 composite treatment could prevent weight loss in mango fruits [27].…”
Section: Weight Losssupporting
confidence: 92%
See 4 more Smart Citations
“…Some recent studies reported that fruit coated with Cs were prevented from reducing in weight, water vapor transmission rate and O 2 /CO 2 by increasing surface and interface roughness and due to a smaller pore size, thus preventing the percentage of weight loss [41]. Menna et al [25] reported Cu-chitosan nano significantly prevented weight loss in tomato during 21 days storage, which is in accordance with our study. Furthermore, chitosan/nano-TiO 2 composite treatment could prevent weight loss in mango fruits [27].…”
Section: Weight Losssupporting
confidence: 92%
“…Application of nano-SiO 2 /chitosan caused an increase of TSS in tomato fruit compared with control [41]. Meena et al [25] reported that Cu-chitosan nano-net treatment significantly prevented the increase of TSS by decreasing respiration and metabolic activities, as a result decreasing sugars in tomato. However, in another study chitosan-silica nanocomposites had no effect on TSS content [48].…”
Section: Tss and Tamentioning
confidence: 99%
See 3 more Smart Citations